2016
DOI: 10.1158/2326-6066.cir-15-0091
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Consumption of Black Raspberries or Their Anthocyanin Constituents Alters Innate Immune Cell Trafficking in Esophageal Cancer

Abstract: Freeze-dried black raspberries (BRB), their component anthocyanins (AC), and a metabolite of BRB ACs, protocatechuic acid (PCA), inhibit the development of esophageal cancer in rats induced by the carcinogen, N-nitrosomethylbenzylamine (NMBA). All three components reduce inflammation in the esophagus and in plasma. The present study determined the relation of changes in inflammatory markers to infiltration of innate immune cells into NMBA-treated esophagus. Rats were injected with NMBA (0.35 mg/kg) for 5 weeks… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
45
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 56 publications
(45 citation statements)
references
References 47 publications
0
45
0
Order By: Relevance
“…Our current study observed significantly increased abundance of Akkermansia by BRB diet and increased abundance of Desulfovibrio by the BRB residue fraction in rats. Previously, we demonstrated that whole BRBs, anthocyanins and the residue fraction decreased cellular proliferation marker Ki67 and inflammatory biomarkers, including cyclooxygenase-2 (COX-2), inducible nitric oxide synthase (iNOS), nuclear factor (NF)-κB, soluble epoxide hydrolase (sEH), pentraxin-3 (PTX3), and prostaglandin E 2 (PGE 2 ), in the NMBA-induced esophageal cancer in rats (11, 43, 44), suggesting that all three diets can suppress tumorigenesis by inhibiting inflammation. In the current study, rats fed whole BRBs or the residue fraction had increased abundance of Akkermansia and Desulfovibrio suggesting that they might contribute to the anti-inflammatory effects of whole BRBs and the residue fraction.…”
Section: Discussionmentioning
confidence: 99%
“…Our current study observed significantly increased abundance of Akkermansia by BRB diet and increased abundance of Desulfovibrio by the BRB residue fraction in rats. Previously, we demonstrated that whole BRBs, anthocyanins and the residue fraction decreased cellular proliferation marker Ki67 and inflammatory biomarkers, including cyclooxygenase-2 (COX-2), inducible nitric oxide synthase (iNOS), nuclear factor (NF)-κB, soluble epoxide hydrolase (sEH), pentraxin-3 (PTX3), and prostaglandin E 2 (PGE 2 ), in the NMBA-induced esophageal cancer in rats (11, 43, 44), suggesting that all three diets can suppress tumorigenesis by inhibiting inflammation. In the current study, rats fed whole BRBs or the residue fraction had increased abundance of Akkermansia and Desulfovibrio suggesting that they might contribute to the anti-inflammatory effects of whole BRBs and the residue fraction.…”
Section: Discussionmentioning
confidence: 99%
“…Our laboratory focuses on chemoprevention of colorectal cancer [4757] and ESCC [3041], using different types of berries. Strawberries have been protective against a number of cancers, including prostate cancer, cervical cancer, ovarian cancer, hepatoma, leukemia, and melanoma [29].…”
Section: Discussionmentioning
confidence: 99%
“…One focus of our laboratory is the chemopreventive effects of berries against ESCC [3041]. Carlton, et al previously demonstrated that both 5% and 10% strawberries reduced the multiplicity of rat esophageal tumors induced by the carcinogen N -nitrosomethylbenzylamine (NMBA) [42].…”
Section: Introductionmentioning
confidence: 99%
“…Our group investigated the ability of BRBs, BRB components (such as AC), and BRB metabolites (such as PCA) to inhibit N-nitrosomethylbenzylamine (NMBA)-induced esophageal cancer and to modulate immune cell trafficking in rats [40]. All rats were injected with NMBA and then they were fed with either a control AIN-76A diet, or the control diet supplemented with either 6.1% of BRB powder (freeze-dried whole BRBs), an AC-rich fraction of BRBs (3.8 μmol/g), or PCA (500 ppm) for 35 weeks.…”
Section: Studies Of Tumor-bearing Animal Modelsmentioning
confidence: 99%